2011
DOI: 10.1111/j.1399-5618.2011.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the glucocorticoid receptor gene in bipolar disorder in an isolated northern Swedish population

Abstract: This study contributes to the growing evidence for a role of the glucocorticoid receptor gene (NR3C1) in vulnerability to mood disorders, and BPD in particular, and warrants further in vitro investigation of the at-risk haplotypes with respect to disease etiology. However, this association might be restricted to this specific population, as it is observed in a rather small sample from an isolated population without replication, and data from large meta-analyses for genome-wide association studies in BPD do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
12
1
1
Order By: Relevance
“…68 On the other hand, we did find an association with polymorphism of the glucocorticoid receptor (NR3C1) gene located on chromosome 5q31−32, 69 implicated in the pathogenesis of bipolar disorder. 70 Positive results have been obtained concerning associations of three genes located on chromosome 22q11−13 with lithium response. A significant association between lithium response and genetic variations in the breakpoint cluster region (BCR) gene located on chromosome 22q11 71 and with the X-box binding protein 1 (XBP1) gene located on chromosome 22q12 72 was found.…”
Section: ■ Clinical Factors Associated With Lithium Efficacymentioning
confidence: 99%
“…68 On the other hand, we did find an association with polymorphism of the glucocorticoid receptor (NR3C1) gene located on chromosome 5q31−32, 69 implicated in the pathogenesis of bipolar disorder. 70 Positive results have been obtained concerning associations of three genes located on chromosome 22q11−13 with lithium response. A significant association between lithium response and genetic variations in the breakpoint cluster region (BCR) gene located on chromosome 22q11 71 and with the X-box binding protein 1 (XBP1) gene located on chromosome 22q12 72 was found.…”
Section: ■ Clinical Factors Associated With Lithium Efficacymentioning
confidence: 99%
“…In addition, exposure to CM has been shown to dysregulate the hypothalamic-pituitary-adrenal (HPA) axis, a master regulator of the body’s stress response (reviewed in (Van Voorhees and Scarpa, 2004)). Substantial work has demonstrated that dysregulation of the HPA axis increases the likelihood of developing mood and anxiety disorders (Appel et al, 2011; Ceulemans et al, 2011; Espejo et al, 2007; Guerry and Hastings, 2011; Nemeroff, 2004). Moreover, it has been well-documented that exposures during early life, including CM, impact DNA methylation (5mC) levels within genes of the HPA axis (Martin-Blanco et al, 2014; McGowan et al, 2009; Romens et al, 2015; van der Knaap et al, 2014) making the HPA axis is a logical starting point for studies examining the epigenetic impact of CM.…”
Section: Introductionmentioning
confidence: 99%
“…Altered GR signaling has also been reported in BD [187][188][189][190], and peripheral blood biomarkers targeting GR proteins and genetic variants [188,[191][192][193][194], mRNA expression [195][196][197], or function [155] have been proposed. Other studies suggested that reduced GR function was related to the dysregulation of GR co-factors such as FKBP5/FKBP51, BAG1, PTGES3, and HSP70 [191,[198][199][200][201][202][203].…”
Section: Glucocorticoid Receptorsmentioning
confidence: 99%